ANOREXIA NERVOSA AND BULIMIA NERVOSA - Sabani, Havva; Baki, Esra (International Scientific Journal Vision, 2024)
Eating disorders are a serious psychopathology type based on the mutual interaction of biological, environmental, psychological, and socio-cultural factors. Individuals are indicated to be at risk for eating disorders from adolescence onwards. The most common eating disorders worldwide are anorexia nervosa and bulimia nervosa; approximately 1% of the general population exhibits symptoms of anorexia nervosa, while 4% shows symptoms of bulimia nervosa. These disorders, which negatively impact an individual’s physiological health, mental health, and life for various reasons, are generally perceived by others in the environment after the illness has become chronic. Anorexia nervosa is characterized by very low body weight, distorted perception of body weight, and intense fear of gaining weight. Bulimia nervosa, on the other hand, is a disorder where individuals secretly consume large portions of food and then try to expel these foods in an unhealthy manner due to subsequent remorse. A multidisciplinary approach is necessary for diagnosing, treating, and monitoring the disease. Screening tests recommended for schools can detect anorexia nervosa and bulimia nervosa patients at an early stage before the disorders become chronic. Patients diagnosed with anorexia nervosa and bulimia nervosa tend to deny their illnesses. During the treatment, CBT, Family therapy, and Cognitive Behavioral Therapy are preferred depending on the patient’s clinical findings to normalize eating behavior and regulate emotions and thoughts.